Incidence of psychosocial factors in public sector employees in the province of Tarma - Medrano-Osorio, Gabriel P. (2021)
Objective. Describe the incidence of psychosocial factors in public sector employees in the province of Tarma. Methods. The type of investigation was basic; descriptive level, descriptive-simple design; The instrument used was the questionnaire on psychosocial factors by Pando et al. (2016), whose dimensions were: workplace conditions, workload, content and characteristics of the task, job demands, job role and career development, social interaction and organizational aspects, and satisfaction with performance compensation; The sample consisted of 120 collaborators from 3 public institutions; the sampling was non-probabilistic - intentional. Results. Psychosocial factors moderately affect the job performance of public sector employees in the province of Tarma. Conclution. The degree of incidence of the factors in the behavior and performance of workers is moderately pernicious, and in the medium term may be a determining aspect in the development and generation of some occupational diseases such as stress and burnout.